A10.2 Anti-AT1R and Anti-Etar Autoantibodies in Pathogenesis of Systemis Sclerosis. (25th February 2013) - Kill, Angela; O Becker, Mike; Guenther, Jeannine; Heidecke, Harald; Dragun, Duska; Riemekasten, Gabriela
Abstract : Background and Objectives: SSc is a prototypic multiorgan disease characterised by vascular damage, autoimmunity and fibrosis with still unkown aetiology. Recently identified functional autoantibodies simultaneously targeting the angiotensin-II type-1 receptor (AT1R-Abs) and the endothelin-1 receptor type A (ETAR-Abs) were linked to vascular and fibrotic complications in SSc. Presence of both autoantibodies moreover predicted mortality due to cardiopulmonary complications implicating their contribution in SSc pathogenesis. Here, autoantibody mediated effects on endothelial cell activation and their blockade by receptor inhibitors were studied. Materials and Methods: Human microdermal endothelial cells-1 (HMEC-1) and human dermal fibroblasts were treated with IgG from SSc patients containing anti-AT1R and anti-ETAR Abs (SSc-IgG) or with IgG from healthy donors (NC-IgG) as negative control. In parallel, SSc-IgG treated cells were incubated with AT1R-and ETAR- antagonists alone and in combination. Activation of endothelial cells was assessed by qRT-PCR and sandwich ELISA and of fibroblasts with immunocytochemistry. Results: Human endothelial cells showed increased expression and production of the pro-inflammatory chemokine interleukin-8 (IL-8) upon treatment with SSc-IgG positive for anti-AT1R and anti-ETAR Abs compared to control treatment with NC-IgG as analysed on mRNA and on protein levels. Furthermore, endothelial cells showed increased expression of the adhesion molecules vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) with SSc-IgG versus NC-IgG treatment on mRNA levels. Expression of IL-8 and VCAM-1 was significantly decreased by receptor inhibition. Human dermal fibroblasts showed increased collagen 1 production upon treatment with SSc-IgG versus NC-IgG that was also reduced by receptor inhibition. Conclusions: Our data sugests a direct involvement of anti-AT1R and anti-ETAR Abs in endothelial cell and fibroblasts activation that is mediated by AT1R and ETAR activation. Increased expression of IL-8 and of VCAM-1 and ICAM-1 indicate a direct endothelial cell activation and inflammation. Increased collagen 1 production indicates fibroblast activation and pro-fibrotic events. Therefore, anti-AT1R and anti-ETAR Abs induce pro-inflammatory and pro-fibrotic events and could be directly involved in the pathogenesis of SSc. In vivo experiments are underway to analyse anti-AT1R and anti-ETAR Abs mediated pathogenic events in SSc.